A light-curing polymer resin material resistant to steel wool and a preparation method thereof
By chemically modifying nanozirconia and combining with specific raw materials, the problem of poor dispersion of inorganic fillers in photocuring resin materials is solved, and the material's wear resistance, adhesion, flexibility and hydrophobicity are significantly improved, achieving better comprehensive performance.
Patent Information
- Application Number
- CN202410860085.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing photocuring resin materials have poor dispersion and agglomeration problems in use, which affects the performance of the product, especially in terms of steel wool resistance.
Modified nanozirconia is used as an inorganic filler, and nanozirconia is chemically modified by a modified silane coupling agent to improve its compatibility and dispersion in the organic system. It is also formed by combining raw materials such as diisocyanate, polyol, and acrylate monomers to form a high-performance photocured polymer resin material.
The wear resistance, adhesion, flexibility and hydrophobicity of photocured polymer resin materials are significantly improved, and the problem of poor dispersion of inorganic fillers is solved, and the overall performance of the material is improved.
Smart Images

Figure BDA0004919024530000021 
Figure BDA0004919024530000031 
Figure FDA0005237551750000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a light-curing polymer resin material resistant to steel wool and a preparation method thereof. Background Art
[0002] Photocurable resin mainly refers to a new type of material that can be rapidly cross-linked and cured into a film under ultraviolet light. UV curing technology has the characteristics of rapid curing, low energy consumption, less pollution, and high efficiency. It has been widely used in many fields such as the coating industry, printing industry, and electronics industry. In recent years, with the increasing awareness of environmental protection, UV curing resin materials have developed rapidly.
[0003] The patent with application number CN201910993077.6 provides an ultra-high steel wool resistant UV light-curing resin, which mainly includes the following raw materials: functional acrylate monomer, isocyanate, inhibitor, catalyst, alcohol compound, acrylate monomer, nano metal oxide. The isocyanate, functional acrylate monomer and alcohol compound in the invention can react, which can effectively improve the steel wool resistance of the ultra-high steel wool resistant UV light-curing resin, so that the ultra-high steel wool resistant UV light-curing resin meets market demand; the patent with application number CN202010068373.8 provides an ultra-wear-resistant steel wool resistant resin, which mainly includes the following raw materials: multi-functional polyurethane acrylate, modified epoxy acrylate, special monomer, additive, photoinitiator, solvent. The invention is achieved by compounding two The invention discloses a polyurethane acrylate with a functional group, and adds a special monomer, modified epoxy acrylate, titanium dioxide as a filler, and carboxymethyl cellulose as a dispersant, which significantly improves the steel wool resistance of the resin film, making it resistant to steel wool pressure of 1KG for 3000 times without leaving a mark, and has good storage stability and low curing shrinkage. The prepared paint film has good adhesion on the surface of the substrate, good flexibility, not easy to crack, and no yellowing under light. The light-curing resin provided by the above patents is added with inorganic fillers. Most of the resin products need to add some inorganic fillers during the processing, whether it is to improve the processing performance or to reduce the production cost of the product. However, in the organic system, the inorganic fillers have problems such as particle agglomeration, which makes it impossible for the inorganic fillers to be completely dispersed and coated in the organic products, thereby seriously affecting the performance of the organic products.
[0004] Therefore, there is an urgent need to develop a photocurable polymer resin material with excellent comprehensive performance that meets market demand. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a light-curable polymer resin material resistant to steel wool and a preparation method thereof. The polymer resin material has excellent comprehensive performance and meets market demand.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0007] A light-curable polymer resin material resistant to steel wool, comprising the following raw materials in parts by weight: 10-20 parts of diisocyanate, 0.3-0.7 parts of catalyst, 0.3-0.7 parts of polymerization inhibitor, 70-90 parts of acrylate monomer, 150-180 parts of polyol, and 5-10 parts of modified nano zirconium oxide;
[0008] The preparation method of the modified nano zirconium oxide is as follows:
[0009] S1. Under stirring conditions, 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate are added to 2-methyltetrahydrofuran in sequence, and the mixture is reacted at 75-85°C for 7-10 hours, cooled to room temperature, filtered, and the filtrate is taken, distilled under reduced pressure, and dried to obtain an intermediate;
[0010] S2. Under stirring conditions, the intermediate obtained in step S1, 4-vinylphenylacetic acid and p-toluenesulfonic acid are added to 2-methyltetrahydrofuran in sequence, and the mixture is reacted at 70-80° C. for 6-12 hours, cooled to room temperature, filtered, and the filtrate is taken and subjected to reduced pressure distillation, extraction, concentration and drying to obtain a modified silane coupling agent;
[0011] S3, dispersing the modified silane coupling agent obtained in step S2 in deionized water to prepare a modified silane solution with a mass fraction of 8-12%; dispersing nano zirconium oxide in ethanol, then adding the modified silane solution, ultrasonicating for 5-15 minutes, stirring and reacting at 70-80° C. for 30-50 minutes, cooling to room temperature, centrifugally separating, washing, and drying to obtain modified nano zirconium oxide;
[0012] Among them, the synthetic route of modified silane coupling agent is as follows:
[0013]
[0014]
[0015] Although the development of nanomaterials is relatively short, they have broad development in many fields due to their excellent thermal, physical and electrochemical properties. Stable nano-zirconia materials have unique physical and chemical properties, high melting point, high hardness, acidity, alkalinity, oxidation and reducibility, and are P-type semiconductors, which are easy to generate holes and can have strong interactions with other active components. It has good applications in many fields such as refractory materials, catalysts, and optoelectronic devices. Nano-zirconia is a common additive for polymer materials, and its addition can significantly improve the mechanical properties and wear resistance of polymer materials. Traditional nano-zirconia has problems such as particle agglomeration, poor dispersibility and unstable structure, so it has been hindered in application. Modifying nano-zirconia to improve the compatibility and dispersibility of nano-zirconia in organic systems has become the key to the research of scientists today. The silane coupling agent is an organic compound with a special structure having two different chemical properties. The invention firstly uses 5,6-epoxyhexyltriethoxysilane and 4,4,4-trifluorobutyric acid as raw materials, and performs a ring-opening reaction under the catalysis of chromium acetate to obtain an intermediate; then uses the intermediate and 4-vinylphenylacetic acid as raw materials, and performs an esterification reaction under the catalysis of p-toluenesulfonic acid to obtain a modified silane coupling agent; then uses the modified silane coupling agent as a modifier to chemically modify nano zirconium oxide to obtain modified nano zirconium oxide, thereby expanding its application range.
[0016] In order to obtain modified nano zirconium oxide and improve its compatibility with organic systems and its dispersibility in organic systems, the molar ratio of 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate in step S1 is 1:0.7-1.0:0.012-0.015, and the amount of 5,6-epoxyhexyltriethoxysilane added to 2-methyltetrahydrofuran is 0.18-0.27 g / mL; the intermediate, 4-vinylphenylacetic acid and p-toluenesulfonic acid in step S2 are The molar ratio of is 1:0.6-0.8:0.02-0.04, the amount of 4-vinylphenylacetic acid added in the 2-methyltetrahydrofuran is 0.10-0.15 g / mL; the mass ratio of the nano zirconium oxide, ethanol, and modified silane solution in step S3 is 1:10-20:20-30, the ultrasonic frequency is 25-35 kHz, and the nano zirconium oxide is dispersed in ethanol by ultrasonic dispersion, the frequency of ultrasonic dispersion is 10-30 kHz, and the time is 30-50 min.
[0017] Furthermore, the polymerization inhibitor is 2,6-di-tert-butylphenol or p-hydroxyanisole; the catalyst is stannous octoate or dibutyltin dilaurate; the diisocyanate is one of isophorone diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl diisocyanate, and hexamethylene diisocyanate; the acrylate monomer is one or more of trimethylolpropane triacrylate, dipentaerythritol pentaacrylate, neopentyl glycol diacrylate, and triethylene glycol diacrylate; the polyol is one of polyethylene glycol, polypropylene glycol, and polycarbonate (1,6-hexanediol) ester diol, and the molecular weight of the polyol is 1000-2500.
[0018] The present invention also provides a method for preparing a light-curing polymer resin material resistant to steel wool, comprising the following steps: adding a polyol to a reactor under a nitrogen atmosphere, removing water at a temperature of 110-120° C., cooling to 70-90° C., sequentially adding a diisocyanate and a catalyst, stirring and reacting for 1-3 hours, then sequentially adding an acrylate monomer and an inhibitor, continuing to stir and react for 2-4 hours, finally adding modified nano zirconium oxide, stirring and reacting for 0.5-1.5 hours, and cooling to room temperature to obtain the light-curing polymer resin material.
[0019] The present invention has the following beneficial effects:
[0020] The invention prepares a modified silane coupling agent by a two-step method, and chemically modifies nano zirconium oxide by using the modified silane coupling agent, and introduces fluorine element, unsaturated bond, benzene ring and siloxane on the surface of nano zirconium oxide; the introduction of fluorine element can reduce the surface tension and friction coefficient of the material, thereby improving the wear resistance of the product; the introduction of siloxane can not only improve the bonding force between materials and the adhesion of the product, but also increase the water contact angle of the material, and improve the hydrophobicity and water resistance of the material; in addition, the introduction of unsaturated bond and siloxane can also make the modified nano zirconium oxide be distributed inside the polymer network material by chemical bonding such as polymerization, so as to give full play to its function; the introduction of benzene ring and other functional groups on the surface of nano zirconium oxide can not only increase its compatibility with the organic system, but also increase the steric hindrance between particles, so that the particles are not easy to agglomerate, and can be evenly distributed in the organic system, and can reduce the amount of inorganic filler under the premise of ensuring the material performance, thereby improving the flexibility of the material.
[0021] The present invention compounds diisocyanate, polyol and acrylate monomers, adds catalysts and polymerization inhibitors, and uses modified nano zirconium oxide as inorganic filler. The components can react with each other, and the wear resistance, adhesion, flexibility and hydrophobicity of the polymer resin material can be significantly improved. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application. The raw materials used in the following embodiments are all common commercially available products.
[0023] Example 1
[0024] A method for preparing modified nano zirconium oxide comprises the following steps:
[0025] S1. Under stirring at 170 rpm, 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate were added to 2-methyltetrahydrofuran in sequence, reacted at 80°C for 8 hours, cooled to room temperature, filtered, and the filtrate was taken. 2-methyltetrahydrofuran was removed by vacuum distillation under reduced pressure, and vacuum dried at 55°C for 12 hours to obtain an intermediate; wherein the molar ratio of 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate was 1:0.8:0.014, and the amount of 5,6-epoxyhexyltriethoxysilane added to 2-methyltetrahydrofuran was 0.22 g / mL;
[0026] S2, under stirring at 170 rpm, add the intermediate obtained in step S1, 4-vinylphenylacetic acid, and p-toluenesulfonic acid to 2-methyltetrahydrofuran in sequence, react at 75° C. for 10 h, cool to room temperature, filter, take the filtrate, remove 2-methyltetrahydrofuran by vacuum distillation, add ethyl acetate and water for extraction (the volume ratio of ethyl acetate to water is 1:1), take the organic phase, concentrate, and vacuum dry at 55° C. for 24 h to obtain a modified silane coupling agent; wherein the molar ratio of the intermediate, 4-vinylphenylacetic acid, and p-toluenesulfonic acid is 1:0.7:0.03, and the amount of 4-vinylphenylacetic acid added to 2-methyltetrahydrofuran is 0.11 g / mL;
[0027] The NMR results of the modified silane coupling agent are: 1 H NMR (300MHz, DMSO-d6) δ7.64 (d, 2H), 7.39 (d, 2H), 6.70-6.74 (m, 1H), 5.76 (d, 1H), 5.18-5.22 (m, 2H), 4.41-4.44 (m, 1H), 4.15-4.18 (m, 1H), 3.81-3.84 (m, 6H), 3.51 (s, 2H), 2.33-2.36 (m, 2H), 2.14-2.18 (m, 2H), 1.47-1.50 (m, 2H), 1.21-1.25 (m, 13H), 0.56 (t, 2H);
[0028] S3, dispersing the modified silane coupling agent obtained in step S2 in deionized water to prepare a modified silane solution with a mass fraction of 10%, and after the preparation is completed, the next step of reaction is carried out within 15 minutes; ultrasonically dispersing nano zirconium oxide in ethanol, the frequency of ultrasonic dispersion is 20kHz, the time is 40 minutes, and then adding the modified silane solution, ultrasonic for 10 minutes, the ultrasonic frequency is 30kHz, stirring and reacting at 75°C for 40 minutes, cooling to room temperature, centrifuging at a speed of 16000r / min for 10 minutes, discarding the supernatant, taking the solid, washing it with deionized water and ethanol respectively, and vacuum drying it at 100°C for 6 hours to obtain modified nano zirconium oxide light yellow powder; wherein the mass ratio of nano zirconium oxide, ethanol, and modified silane solution is 1:15:25.
[0029] The grafting rate of the modified nano-zirconia prepared in this example was measured. The mass of the empty crucible was weighed with an electronic analytical balance, and the dried modified nano-zirconia was added. The crucible with the modified nano-zirconia sample was weighed again, and the data was recorded. The muffle furnace was set to 600°C, and the sample was weighed again after high-temperature calcination for 6 hours. The grafting rate of the modified nano-zirconia was calculated. The calculation formula is: Grafting rate (%) = (M 前 -M 后 ) / M 前 ×100%, where M 前 is the mass of modified nano-zirconia before calcination, M 后 The mass of the modified nano-zirconia after calcination was 3.2% of the grafting rate of the modified nano-zirconia. The particle size of the modified nano-zirconia was 30-60 nm as measured by the NKT5100 laser particle size analyzer.
[0030] A light-curable polymer resin material resistant to steel wool comprises the following raw materials in parts by weight: 15 parts of diisocyanate, 0.5 parts of catalyst, 0.5 parts of polymerization inhibitor, 80 parts of acrylate monomer, 160 parts of polyol and 7 parts of modified nano zirconium oxide; wherein the polymerization inhibitor is p-hydroxyanisole; the diisocyanate is methylcyclohexyl diisocyanate, the catalyst is dibutyltin dilaurate, the acrylate monomer is prepared by mixing equal masses of trimethylolpropane triacrylate and neopentyl glycol diacrylate; the polyol is polyethylene glycol, and the molecular weight of the polyethylene glycol is 2000.
[0031] A method for preparing a light-curing polymer resin material resistant to steel wool comprises the following steps: adding polyol to a reactor under a nitrogen atmosphere, dehydrating at 115°C (dehydration time is 2 hours), cooling to 80°C, sequentially adding diisocyanate and a catalyst, stirring and reacting for 2 hours, then sequentially adding an acrylate monomer and an inhibitor, continuing to stir and react for 3 hours, finally adding modified nano zirconium oxide, stirring and reacting for 1 hour, and cooling to room temperature to obtain the light-curing polymer resin material.
[0032] Example 2
[0033] A method for preparing modified nano-zirconia is prepared according to the method described in Example 1, except that: in step S3, the mass fraction of the modified silane solution is 8%, and the mass ratio of nano-zirconia, ethanol, and modified silane solution is 1:20:30. The prepared modified nano-zirconia has a grafting rate of 2.9% and a particle size of 35-55 nm.
[0034] A light-curable polymer resin material resistant to steel wool comprises the following raw materials in parts by weight: 10 parts of diisocyanate, 0.3 parts of catalyst, 0.7 parts of polymerization inhibitor, 90 parts of acrylate monomer, 180 parts of polyol, and 10 parts of modified nano zirconium oxide prepared in Example 1; wherein the polymerization inhibitor is p-hydroxyanisole; the diisocyanate is dicyclohexylmethane diisocyanate, the catalyst is stannous octoate, the acrylate monomer is prepared by mixing equal masses of trimethylolpropane triacrylate and neopentyl glycol diacrylate; the polyol is polypropylene glycol, and the molecular weight of the polypropylene glycol is 2000.
[0035] A method for preparing a light-curing polymer resin material resistant to steel wool comprises the following steps: adding polyol to a reactor under a nitrogen atmosphere, dehydrating at 115° C. (dehydration time is 2 hours), cooling to 70° C., sequentially adding diisocyanate and a catalyst, stirring and reacting for 2 hours, then sequentially adding an acrylate monomer and an inhibitor, continuing to stir and react for 3 hours, finally adding modified nano zirconium oxide, stirring and reacting for 1 hour, and cooling to room temperature to obtain the light-curing polymer resin material.
[0036] Example 3
[0037] A method for preparing modified nano-zirconia is prepared according to the method described in Example 1, except that: in step S3, the mass fraction of the modified silane solution is 12%, and the mass ratio of nano-zirconia, ethanol, and modified silane solution is 1:10:20. The prepared modified nano-zirconia has a grafting rate of 3.1% and a particle size of 40-60 nm.
[0038] A light-curable polymer resin material resistant to steel wool comprises the following raw materials in parts by weight: 20 parts of diisocyanate, 0.7 parts of catalyst, 0.3 parts of polymerization inhibitor, 70 parts of acrylate monomer, 150 parts of polyol, and 5 parts of modified nano zirconium oxide prepared in Example 1; wherein the polymerization inhibitor is 2,6-di-tert-butylphenol; the diisocyanate is hexamethylene diisocyanate, the catalyst is dibutyltin dilaurate, the acrylate monomer is prepared by mixing equal masses of dipentaerythritol pentaacrylate and triethylene glycol diacrylate; the polyol is polyethylene glycol, and the molecular weight of the polyethylene glycol is 2000.
[0039] A method for preparing a light-curing polymer resin material resistant to steel wool comprises the following steps: adding polyol to a reactor under a nitrogen atmosphere, dehydrating at 115°C (dehydration time is 2 hours), cooling to 90°C, sequentially adding diisocyanate and a catalyst, stirring and reacting for 2 hours, then sequentially adding an acrylate monomer and an inhibitor, continuing to stir and react for 3 hours, finally adding modified nano zirconium oxide, stirring and reacting for 1 hour, and cooling to room temperature to obtain the light-curing polymer resin material.
[0040] Comparative Example 1
[0041] A method for preparing modified nano-zirconium oxide is prepared according to the method described in Example 1, except that in step S3, the mass ratio of nano-zirconium oxide, ethanol, and modified silane solution is 1:10:10.
[0042] A light-curable polymer resin material resistant to steel wool and a preparation method thereof are prepared according to the method described in Example 1.
[0043] Comparative Example 2
[0044] A method for preparing modified nano zirconium oxide comprises the following steps:
[0045] 5,6-epoxyhexyltriethoxysilane was dispersed in deionized water to prepare a silane solution with a mass fraction of 10%. After the preparation, the next step of reaction was carried out within 15 minutes. Nano-zirconia was ultrasonically dispersed in ethanol at a frequency of 20kHz for 40 minutes. Then, the silane solution was added and ultrasonicated for 10 minutes at a frequency of 30kHz. The mixture was stirred at 75°C for 40 minutes, cooled to room temperature, centrifuged at 16000r / min for 10 minutes, the supernatant was discarded, the solid was taken, washed with deionized water and ethanol respectively, and vacuum dried at 100°C for 6 hours to obtain modified nano-zirconium oxide. The mass ratio of nano-zirconium oxide, ethanol and silane solution was 1:15:25.
[0046] A light-curable polymer resin material resistant to steel wool and a preparation method thereof are prepared according to the method described in Example 1.
[0047] Comparative Example 3
[0048] A light-curable polymer resin material resistant to steel wool comprises the following raw materials in parts by weight: 15 parts of diisocyanate, 0.5 parts of catalyst, 0.5 parts of polymerization inhibitor, 80 parts of acrylate monomer, 160 parts of polyol and 10 parts of nano zirconium oxide; wherein the polymerization inhibitor is p-hydroxyanisole; the diisocyanate is methylcyclohexyl diisocyanate, the catalyst is dibutyltin dilaurate, the acrylate monomer is prepared by mixing equal masses of trimethylolpropane triacrylate and neopentyl glycol diacrylate; the polyol is polyethylene glycol, and the molecular weight of the polyethylene glycol is 2000.
[0049] A method for preparing a light-curable polymer resin material resistant to steel wool is prepared according to the method described in Example 1.
[0050] The photocurable polymer resin materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to relevant performance tests. The photocurable polymer resin materials prepared in Examples 1-3 and Comparative Examples 1-3 were uniformly coated on an ABS substrate with a coating thickness of 15 μm, and then subjected to UV curing treatment with a photocuring energy of 800 mJ / cm 2 , time is 2min, and a photocurable polymer resin film is obtained. The RCA wear resistance test adopts Norman RCA wear resistance tester, and the resin film is carried out under the condition of 180g load; the steel wool resistance test steel wool model (#0000), size 2cm×2cm, stroke 4cm, speed 50 times / min, load 1kg; the adhesion performance test is carried out in accordance with the relevant provisions of GB / T9286-2021 "Paint and Varnish Scratching Test"; the water contact angle test adopts a static water contact angle meter, and the reading is read within 6 seconds of dripping; the flexibility test is carried out in accordance with the relevant provisions of GB / T1731-1993 "Paint Film Flexibility Determination Method"; the above tests are repeated three times and the average value is taken. The test results are shown in Table 1. It can be seen from the data in Table 1 that compared with Comparative Examples 1-3, the photocurable polymer resin materials prepared in Examples 1-3 have better wear resistance, adhesion, flexibility and water contact angle, among which the comprehensive performance of the photocurable polymer resin material prepared in Example 1 is the best.
[0051] Table 1 Test results of relevant properties of light-curing polymer resin materials
[0052] Test items Steel wool wear resistance / times RCA wear resistance / times Adhesion / Grade Flexibility / mm Water contact angle / ° Example 1 650 1150 0 1 118 Example 2 600 1050 0 1 114 Example 3 600 1100 0 1 117 Comparative Example 1 500 900 0 2 101 Comparative Example 2 450 800 1 2 92 Comparative Example 3 400 750 2 3 86
[0053] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A light-curable polymer resin material resistant to steel wool, characterized in that: The method comprises the following raw materials in parts by weight: 10-20 parts of diisocyanate, 0.3-0.7 parts of catalyst, 0.3-0.7 parts of polymerization inhibitor, 70-90 parts of acrylate monomer, 150-180 parts of polyol, and 5-10 parts of modified nano zirconium oxide; The preparation method of the modified nano zirconium oxide is as follows: S1. Under stirring conditions, 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate were added to 2-methyltetrahydrofuran in sequence, and the mixture was reacted at 75-85°C for 7-10 hours. The mixture was cooled to room temperature, filtered, and the filtrate was taken and subjected to reduced pressure distillation and drying to obtain an intermediate. The structural formula of the intermediate is: S2. Under stirring conditions, the intermediate obtained in step S1, 4-vinylphenylacetic acid and p-toluenesulfonic acid are added to 2-methyltetrahydrofuran in sequence, and the mixture is reacted at 70-80° C. for 6-12 hours, cooled to room temperature, filtered, and the filtrate is distilled under reduced pressure, extracted, concentrated and dried to obtain a modified silane coupling agent. The structural formula of the modified silane coupling agent is: S3, dispersing the modified silane coupling agent obtained in step S2 in deionized water to prepare a modified silane solution with a mass fraction of 8-12%; dispersing nano zirconium oxide in ethanol, then adding the modified silane solution, ultrasonicating for 5-15 minutes, stirring and reacting at 70-80° C. for 30-50 minutes, cooling to room temperature, centrifugally separating, washing, and drying to obtain modified nano zirconium oxide; The mass ratio of nano zirconium oxide, ethanol and modified silane solution in step S3 is 1:10-20:20-30.
2. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The molar ratio of 5,6-epoxyhexyltriethoxysilane, 4,4,4-trifluorobutyric acid and chromium acetate in step S1 is 1:0.7-1.0:0.012-0.015, and the amount of 5,6-epoxyhexyltriethoxysilane added to the 2-methyltetrahydrofuran is 0.18-0.27 g / mL.
3. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The molar ratio of the intermediate, 4-vinylphenylacetic acid and p-toluenesulfonic acid in step S2 is 1:0.6-0.8:0.02-0.04, and the amount of 4-vinylphenylacetic acid added to the 2-methyltetrahydrofuran is 0.10-0.15 g / mL.
4. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The ultrasonic frequency in step S3 is 25-35kHz.
5. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: In step S3, the nano-zirconium oxide is dispersed in ethanol by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 10-30kHz and the time is 30-50min.
6. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The polymerization inhibitor is 2,6-di-tert-butylphenol or p-hydroxyanisole; and the catalyst is stannous octoate or dibutyltin dilaurate.
7. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The diisocyanate is one of isophorone diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexyl diisocyanate and hexamethylene diisocyanate.
8. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The acrylate monomer is one or more of trimethylolpropane triacrylate, dipentaerythritol pentaacrylate, neopentyl glycol diacrylate and triethylene glycol diacrylate.
9. The light-curable polymer resin material resistant to steel wool according to claim 1, characterized in that: The polyol is one of polyethylene glycol, polypropylene glycol and poly(1,6-hexanediol) carbonate diol.
10. The method for preparing a light-curable polymer resin material resistant to steel wool according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding polyol into a reactor under a nitrogen atmosphere, removing water at a temperature of 110-120° C., cooling to 70-90° C., sequentially adding diisocyanate and a catalyst, stirring and reacting for 1-3 hours, then sequentially adding an acrylate monomer and an inhibitor, continuing to stir and react for 2-4 hours, finally adding modified nano zirconium oxide, stirring and reacting for 0.5-1.5 hours, and cooling to room temperature to obtain a light-curing polymer resin material.
Citation Information
Patent Citations
A UV-curable resin with ultra-high resistance to steel wool and its preparation method
CN110643276B
UV-curing resin with ultra-high resistance to steel wool and preparation method of UV-curing resin
CN110643276A
Steel wool-resistant super wear-resistant resin
CN111234684A